2012
DOI: 10.1111/j.1476-5381.2012.01972.x
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of β‐adrenoceptors restores the GRK2‐mediated adrenal α2‐adrenoceptor–catecholamine production axis in heart failure

Abstract: BACKGROUND AND PURPOSE Sympathetic nervous system (SNS) hyperactivity is characteristic of chronic heart failure (HF) and significantly worsens prognosis. The success of β‐adrenoceptor antagonist (β‐blockers) therapy in HF is primarily attributed to protection of the heart from the noxious effects of augmented catecholamine levels. β‐Blockers have been shown to reduce SNS hyperactivity in HF, but the underlying molecular mechanisms are not understood. The GPCR kinase‐2 (GRK2)–α2adrenoceptor–catecholamine produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 47 publications
0
46
0
2
Order By: Relevance
“…2). 8185 This emerging crucial role for adrenal GRK2 in HF is underlined by the fact that its specific inhibition, via adenoviral-mediated βARKct adrenal gene delivery (see below), leads to a significant reduction in circulating catecholamine levels, restoring not only adrenal, but also cardiac function in HF. 81 Additional evidence for the crucial role of adrenal GRK2-regulated α 2 ARs in regulating adrenal ANS tone in HF comes from the phenylethanolamine-N-methyl transferase (PNMT)-driven GRK2 KO mice.…”
Section: Regulation Of Ans Outflow and Activity In Health And In Chronimentioning
confidence: 99%
See 1 more Smart Citation
“…2). 8185 This emerging crucial role for adrenal GRK2 in HF is underlined by the fact that its specific inhibition, via adenoviral-mediated βARKct adrenal gene delivery (see below), leads to a significant reduction in circulating catecholamine levels, restoring not only adrenal, but also cardiac function in HF. 81 Additional evidence for the crucial role of adrenal GRK2-regulated α 2 ARs in regulating adrenal ANS tone in HF comes from the phenylethanolamine-N-methyl transferase (PNMT)-driven GRK2 KO mice.…”
Section: Regulation Of Ans Outflow and Activity In Health And In Chronimentioning
confidence: 99%
“…121 In addition, restoration of adrenal GRK2-α 2 AR-catecholamine secretion axis and suppression of NE release from cardiac ANS endings might contribute to the beneficial effects of β-blockers in chronic HF, as well. 74,85 …”
Section: Ans Therapeutics In Hfmentioning
confidence: 99%
“…Interestingly, exercise in HF was also found to not only improve GRK2 levels and β-AR signaling in the heart, but also lead to reduction of GRK2 levels in the adrenal gland supporting the notion that these sympatholytic effects can improve cardiac responses [78]. β-blockers also appear to have the capacity to lower GRK2 levels in both the heart and the adrenal gland, which appears critical to any sympatholytic effect of this HF therapy [79]. …”
Section: Grk2 Regulation Of Cardiac β-Ars In Health and Hfmentioning
confidence: 97%
“…Indeed, recent studies have demonstrated that β-blockers can ameliorate clinical outcomes in HF also by reducing adrenal GRK2 levels, thus normalizing catecholamine release by restoring the negative feedback mediated by α2AR (bisoprolol)32 or by increasing vascular endothelial growth factor signaling, thus stimulating neoangiogenesis (atenolol and bisoprolol) 33…”
Section: The Ar System In Hfmentioning
confidence: 99%